Flexural behavior of the fast-hardening anti-disturbance concrete wet-joint beam after vibration of solidification period - Chang Liu; Jinsheng Du; Ziang Sun; Licun Yu; Yuzhuo Wang (Case Studies in Construction Materials)
This paper presented the flexural behavior of the fast-hardening anti-disturbance concrete (FHADC) wet-joint beam after vibration of solidification period. Considering the influence factors of amplitude and frequency, 10 FHADC wet-joint beams were vibrated during solidification, then the beams were subjected to bending test. The results showed that: (1)The failure mode of wet-joint beams was bending-shear failure. (2)Simple harmonic vibration can cause more serious damage on beams, compared with low-cycle reciprocating vibration. The crack size increase with the increasing amplitude and frequency of the applied vibration. (3)Under low-cycle reciprocating vibration, the ultimate load of beam decreased by 1.8 % with the amplitude increased. (4)Under simple harmonic vibration, the ultimate load of beam decreased by 36.8 % with the increase of amplitude and decreased by 20.4 % with the increase of frequency. Finally, a calculation method for the flexural capacity of wet-joint beams has been proposed, which offers a reference for similar engineering design.